Hazardous household waste management in Vinnytsia region - Ishchenko, Vitalii; Petruk, Roman; Kozak, Yana (Publishing House of Lviv Polytechnic National University, 2016)
The article analyzes hazardous household waste, including detergents, paints, adhesives, expired medicines, luminescent lamps, pesticides, fertilizers, batteries and accumulators, electrical and electronic waste, mercury-containing materials. Research shows that they contain a large quantity of dangerous and toxic substances (compounds of heavy metals, chlorinated polymers, aromatic hydrocarbons, surfactants, etc.), which pose a significant risk to the environment and human. The analysis of hazardous household waste management in the Vinnytsia region has showed absence of the appropriate management system. Hazardous household waste is collected separately only fragmentary and is released into environment together with other household waste, creating an environmental hazard in the region. The article also contains recommendations for the hazardous household waste management.
Keywords: hazardous household waste; toxic substances; waste management; batteries; luminescent lamps; mercury-containing materials; detergents